Under the Hood of Activist Fraud Campaigns: Private Information Quality, Disclosure Incentives, and Stock Lending Dynamics - Ahn, Byung Hyun; Bushman, Robert M.; Patatoukas, Panos N. (The Accounting Review, 2024)
ABSTRACT Although activist short sellers can play a crucial role in fraud detection, they have come under scrutiny following accusations of systematically disseminating false negative information. We develop a framework delineating the roles of campaign-specific private information quality and short-selling dynamics in shaping disclosure incentives. We predict that the act of disclosure combined with pre-disclosure stock lending dynamics is informative about the quality of an activist’s private information. We find that increased pre-disclosure shorting intensity is associated with more negative post-disclosure returns, adverse media coverage, and consequential campaign outcomes, including auditor turnover, accounting restatements, class-action lawsuits, and performance-related delistings. Furthermore, elevated short-selling costs and risks magnify the association between pre-disclosure shorting intensity and post-disclosure underperformance. Finally, we examine V-shaped reversals and short covering following activists’ disclosures and find no evidence of systematic manipulation. We conclude that activists disclosing fraud allegations under their own names are discouraged from engaging in “short-and-distort” schemes. Data Availability: Data are available from the sources cited in the text. JEL Classifications: G12; G14; G23; M41.